A tough PE pipe and preparation method thereof
By adopting different formulas of inner and outer layers and composite co-extrusion technology in PE pipes, the problems of insufficient UV resistance and brittle breakage of PE pipes are solved, and the effect of improving anti-aging and mechanical toughness is achieved.
Patent Information
- Application Number
- CN202410375605.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-03-29
AI Technical Summary
PE pipes have insufficient UV resistance, and they are prone to aging and mechanical properties when exposed to sunlight for a long time. At the same time, they are prone to brittle breakage after adding carbon black, which affects the application.
Tough PE pipes with different formulas of the inner and outer layers are used. The inner layer is composed of LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant. The outer layer is composed of HDPE, carbon black masterbatch and antioxidant. It is prepared through composite coextrusion technology to improve the dispersion and stability of carbon black.
It improves the resistance to UV aging and mechanical toughness of PE pipes, avoids brittle damage, and enhances the overall durability of the pipes.
Smart Images

Figure CN118185156B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic pipes, and in particular to a tough PE pipe and a preparation method thereof. Background Art
[0002] PE pipes are polyethylene pipes. PE pipes occupy an important position among many types of plastic pipes. PE pipes have durable properties such as wear resistance and corrosion resistance, and have a long service life. PE pipes are also light and easy to construct. Therefore, PE pipes are used in water supply and drainage, gas transportation, and mining mortar transportation.
[0003] One of the disadvantages of PE pipes is their insufficient resistance to UV rays. Long-term exposure to sunlight can easily cause aging of PE pipes and degradation of their mechanical properties, which imposes stringent requirements on the transportation, storage and construction of PE pipes.
[0004] For this reason, carbon black is generally added to PE pipes, which can effectively reduce the efficiency of photodegradation of PE pipes, thereby improving the aging resistance of PE pipes. However, in actual applications, it is found that PE pipes become more brittle after adding carbon black, which affects the application of PE pipes that need to be buried deep underground and withstand pressure. Summary of the invention
[0005] In order to improve the aging resistance of PE pipes and improve the problem of brittle fracture of PE pipes, the present application provides a tough PE pipe and a preparation method thereof.
[0006] In the first aspect, the present application provides a tough PE pipe adopting the following technical solution:
[0007] A tough PE pipe comprises an inner layer and an outer layer, wherein the inner layer is made of a raw material comprising LDPE, a carbon black masterbatch, a styrene-olefin copolymer and an antioxidant, and the outer layer is made of a raw material comprising HDPE, a carbon black masterbatch and an antioxidant;
[0008] The carbon black masterbatch is made from the following raw materials in parts by weight:
[0009] 8-16 parts of carbon black;
[0010] LDPE 13-22 parts;
[0011] 0.45-0.8 parts of ethylene-methacrylic acid copolymer;
[0012] 0.1-0.25 parts of styrene-acrylic acid copolymer;
[0013] Nucleating agent 0.05-0.1 parts.
[0014] By adopting the above technical solution, LDPE refers to low-density polyethylene, and HDPE refers to high-density polyethylene, which can meet the different performance requirements of the inner and outer layers of the pipe. The carrier resin of the carbon black masterbatch is LDPE, so that the carbon black can be pre-dispersed, and the carbon black can be better and more evenly dispersed in the polyethylene system when the pipe is formed. Since the surface of carbon black is hydrophilic, ethylene-methacrylic acid copolymer is added to make the surface of carbon black hydrophobic and adapt to the hydrophobic properties of LDPE. The ethylene segment of ethylene-methacrylic acid copolymer is similar to the structure of LDPE. The combination of nucleating agent can improve the polyethylene crystal structure and make the ethylene-methacrylic acid copolymer and LDPE moderately entangled, so that the compatibility of carbon black and LDPE is high, and the composition of carbon black masterbatch is more uniform, which ultimately improves the toughness of PE pipes and resistance to brittle damage. While improving the resistance of pipes to ultraviolet aging, the durability is improved.
[0015] Styrene-olefin copolymer is also added to the inner layer, combined with styrene-acrylic copolymer in the carbon black masterbatch, and the structural rigidity of the styrene structural chain segment is used to improve the stability of carbon black in the polyethylene system. In addition, styrene-olefin copolymer is suitable for entanglement in the LDPE structural system, thereby further improving the toughness of the pipe and increasing the applicable temperature range.
[0016] Optionally, the mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer is 9 to 12%.
[0017] By adopting the above technical solution, the content of methacrylic acid is controlled within the above range, which has a good effect on the hydrophobic modification of the carbon black masterbatch, thereby improving the dispersibility of carbon black in the PE pipe.
[0018] Optionally, the weight ratio of LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant in the inner layer is 100:(5-8):(2-4):(0.5-0.8); the weight ratio of HDPE, carbon black masterbatch and antioxidant in the outer layer is 100:(6-10.5):(0.5-0.8).
[0019] By adopting the above technical solution, based on the different environments faced by the inner and outer layers when the pipe is used, and the addition of styrene-olefin copolymer to the inner layer, the inner and outer layers respectively use specific PE and carbon black masterbatch ratios, so that the inner and outer layers can be stably combined to improve durability.
[0020] Optionally, the styrene-olefin copolymer is selected from one or both of styrene-butadiene copolymer and styrene-isoprene copolymer.
[0021] By adopting the above technical solution, the above styrene-olefin copolymers can play a role in improving the durability of PE pipes.
[0022] Optionally, the styrene-olefin copolymer is a styrene-isoprene copolymer, and the mass fraction of isoprene in the styrene-isoprene copolymer is 20-27%.
[0023] By adopting the above technical scheme and selecting a styrene-isoprene copolymer with a specific isoprene content, the carbon black can be stabilized while reducing the impact on the anti-photodegradation effect of the carbon black, thereby maintaining the PE pipe with good anti-ultraviolet effect, and the toughness of the PE pipe is improved, making it less prone to brittle failure.
[0024] Optionally, the nucleating agent is one or more of talc, wollastonite, silicon dioxide, sorbitol nucleating agents and stearate nucleating agents.
[0025] By adopting the above technical solution and selecting the above nucleating agent, the processing performance of the carbon black masterbatch can be made more suitable for PE pipes.
[0026] Optionally, the nucleating agent is a combination of vinyl silane coupling agent modified wollastonite and potassium stearate in a weight ratio of 1:(3-5).
[0027] By adopting the above technical scheme, an inorganic nucleating agent and an organic nucleating agent are compounded, the surface compatibility of wollastonite modified by a vinyl silane coupling agent with potassium stearate is improved, the melt dispersibility of the carbon black masterbatch in the PE system is higher, and finally the pressure resistance of the PE pipe is improved.
[0028] In the second aspect, the present application provides a method for preparing a tough PE pipe using the following technical solution:
[0029] A method for preparing a tough PE pipe comprises the following steps:
[0030] The carbon black, LDPE, ethylene-methacrylic acid copolymer and nucleating agent are put into an extruder for mixing, extruding, cooling and granulating to obtain a carbon black masterbatch;
[0031] LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant are used as inner layer raw materials and put into an extruder for extrusion to obtain an inner layer fluid, HDPE, carbon black masterbatch and antioxidant are used as outer layer raw materials and put into another extruder for extrusion to obtain an outer layer fluid, and then the inner layer fluid and the outer layer fluid are compositely co-extruded through a co-extrusion die head, cooled, and a tough PE pipe is obtained.
[0032] By adopting the above technical solution, a tough PE pipe is produced by composite co-extrusion, integrating the characteristics of the inner layer and the outer layer, so that the overall durability and mechanical properties of the tough PE pipe are better.
[0033] Optionally, the nucleating agent is a combination of vinyl silane coupling agent modified wollastonite and potassium stearate in a weight ratio of 1:(3-4). The preparation method of the vinyl silane coupling agent modified wollastonite is as follows: dispersing wollastonite in a solvent, adding a vinyl silane coupling agent, heating for reaction, filtering after the reaction is completed, and obtaining vinyl silane coupling agent modified wollastonite.
[0034] By adopting the above technical solution, the vinyl silane coupling agent not only reduces the hydrophilicity of the surface of wollastonite and improves the surface compatibility with potassium stearate, but also promotes the connection between wollastonite and the polyethylene system, thereby improving the pressure resistance of the PE pipe.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. The present application adopts ethylene-methacrylic acid copolymer and styrene-acrylic acid copolymer to jointly improve the dispersion uniformity of carbon black in the carbon black masterbatch. The ethylene segment of the ethylene-methacrylic acid copolymer is similar to the LDPE structure. The combination of a nucleating agent can improve the polyethylene crystal structure, so that the ethylene-methacrylic acid copolymer and the LDPE are moderately entangled with each other, thereby the carbon black and LDPE have high compatibility, and the structural rigidity of the styrene structure segment is used to improve the stability of carbon black in the polyethylene system, thereby improving the durability and mechanical toughness of the pipe.
[0037] 2. The present application also selects a styrene-isoprene copolymer with a specific isoprene content, which can stabilize the carbon black while reducing the impact on the anti-photodegradation effect of the carbon black, thereby maintaining the PE pipe with good anti-ultraviolet effect, and the toughness of the PE pipe is improved, making it less prone to brittle failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic cross-sectional view of the pipe of Example 1 of the present application.
[0039] Description of reference numerals:
[0040] 1. Inner layer; 2. Outer layer. DETAILED DESCRIPTION
[0041] The following is combined with Figure 1 This application is described in further detail.
[0042] The LDPE of the inner layer was purchased from Dow LDPE 722; the LDPE of the carbon black masterbatch was purchased from Dow LDPE 582E; and the HDPE of the outer layer was purchased from Dow HDPE 80017.
[0043] Styrene-acrylic acid copolymer was purchased from BASF as Joncryl7124.
[0044] The carbon black used has a particle size range of 20 to 40 nm.
[0045] The antioxidant used is antioxidant 1010.
[0046] The manufacturer models or parameters disclosed above are used to support the full disclosure of this application, but are not limited to the listed manufacturer models and parameters.
[0047] Preparation Example Preparation method of vinyl silane coupling agent modified wollastonite:
[0048] Disperse 500 g of wollastonite in 4 L of ethanol, dropwise add 5 g of vinyl silane coupling agent, specifically KH-570, heat to 65° C. and stir to react for 1 h. After the reaction is completed, filter, wash with ethanol and water, and dry to obtain vinyl silane coupling agent-modified wollastonite.
[0049] Example 1
[0050] Preparation method of carbon black masterbatch:
[0051] Weigh 8 kg of carbon black, 13 kg of LDPE, 0.45 kg of ethylene-methacrylic acid copolymer, 0.1 kg of styrene-acrylic acid copolymer and 0.05 kg of nucleating agent, wherein the mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer is 9%, and potassium stearate is selected as the nucleating agent.
[0052] Carbon black, LDPE, ethylene-methacrylic acid copolymer, styrene-acrylic acid copolymer and nucleating agent were premixed at 70° C. for 30 minutes, then put into an extruder for mixing, extruded at 150° C., cooled and granulated to obtain a carbon black masterbatch.
[0053] Preparation method of tough PE pipe:
[0054] 10 kg LDPE, 0.5 kg carbon black masterbatch, 0.2 kg styrene-olefin copolymer and 0.05 kg antioxidant were weighed as inner layer raw materials, wherein the styrene-olefin copolymer is specifically a styrene-isoprene copolymer, and the mass fraction of isoprene in the styrene-isoprene copolymer is 12%.
[0055] Weigh 10 kg of HDPE, 0.6 kg of carbon black masterbatch and 0.05 kg of antioxidant as raw materials for the outer layer.
[0056] The inner layer raw materials are premixed at 70°C for 30 minutes, then put into an extruder for mixing and extruded at 170°C to obtain the inner layer fluid; the outer layer raw materials are premixed at 80°C for 30 minutes, then put into another extruder for mixing and extruded at 195°C to obtain the outer layer fluid, and then the inner layer fluid and the outer layer fluid are compound co-extruded through a co-extrusion die head and cooled to obtain a tough PE pipe, such as Figure 1As shown, the tough PE pipe consists of an inner layer 1 and an outer layer 2, and the thickness ratio of the inner layer 1 to the outer layer 2 is 0.8:1.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that in the process of preparing the carbon black masterbatch, the raw materials weighed are different; in the process of preparing the tough PE pipe, the inner layer raw material and the outer layer raw material weighed are different.
[0059] In the process of preparing carbon black masterbatch, 16 kg of carbon black, 22 kg of LDPE, 0.8 kg of ethylene-methacrylic acid copolymer, 0.25 kg of styrene-acrylic acid copolymer and 0.1 kg of nucleating agent were weighed, wherein the mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer was 9%, and potassium stearate was selected as the nucleating agent.
[0060] In the process of preparing the tough PE pipe, 10kg LDPE, 0.6kg carbon black masterbatch, 0.3kg styrene-olefin copolymer and 0.06kg antioxidant are weighed as the inner layer raw materials, wherein the styrene-olefin copolymer is specifically styrene-butadiene copolymer, and the mass fraction of butadiene in the styrene-butadiene copolymer is 60%; 10kg HDPE, 0.85kg carbon black masterbatch and 0.06kg antioxidant are weighed as the outer layer raw materials.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that in the process of preparing the carbon black masterbatch, the raw materials weighed are different; in the process of preparing the tough PE pipe, the inner layer raw material and the outer layer raw material weighed are different.
[0063] In the process of preparing carbon black masterbatch, 13 kg of carbon black, 20 kg of LDPE, 0.6 kg of ethylene-methacrylic acid copolymer, 0.15 kg of styrene-acrylic acid copolymer and 0.06 kg of nucleating agent were weighed, wherein the mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer was 9%, and potassium stearate was selected as the nucleating agent.
[0064] In the process of preparing the tough PE pipe, 10kg LDPE, 0.8kg carbon black masterbatch, 0.4kg styrene-olefin copolymer and 0.08kg antioxidant are weighed as the inner layer raw materials, wherein the styrene-olefin copolymer is specifically a styrene-isoprene copolymer, and the mass fraction of isoprene in the styrene-isoprene copolymer is 12%; 10kg HDPE, 1.05kg carbon black masterbatch and 0.08kg antioxidant are weighed as the outer layer raw materials.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 3 is that, in the process of preparing the carbon black masterbatch, the mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer used is 12%.
[0067] Example 5
[0068] The difference between this embodiment and embodiment 3 is that, in the process of preparing the carbon black masterbatch, the nucleating agent used is a mixture of 0.45 kg potassium stearate and 0.15 kg wollastonite.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 3 is that, in the process of preparing the carbon black masterbatch, the nucleating agent used is a mixture of 0.45 kg of potassium stearate and 0.15 kg of vinyl silane coupling agent modified wollastonite obtained in the preparation example.
[0071] Example 7
[0072] The difference between this embodiment and embodiment 3 is that, in the process of preparing the carbon black masterbatch, the nucleating agent used is a mixture of 0.5 kg of potassium stearate and 0.1 kg of vinyl silane coupling agent modified wollastonite obtained in the preparation example.
[0073] Example 8
[0074] The difference between this embodiment and embodiment 3 is that, in the process of preparing the tough PE pipe, the mass fraction of isoprene in the styrene-isoprene copolymer is 20%.
[0075] Example 9
[0076] The difference between this embodiment and embodiment 3 is that, in the process of preparing the tough PE pipe, the mass fraction of isoprene in the styrene-isoprene copolymer is 27%.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 3 is that, during the preparation of the carbon black masterbatch, no ethylene-methacrylic acid copolymer is added.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 3 is that, during the preparation of the carbon black masterbatch, no nucleating agent potassium stearate is added.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 3 is that, in the process of preparing the carbon black masterbatch, an equal amount of styrene-isoprene copolymer is used to replace the styrene-acrylic acid copolymer, and the mass fraction of isoprene in the styrene-isoprene copolymer is 12%.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 3 is that, in the process of preparing the tough PE pipe, the styrene-isoprene copolymer is added as the outer layer raw material instead, that is, the inner layer raw material comprises LDPE, carbon black masterbatch and antioxidant, and the outer layer raw material comprises HDPE, carbon black masterbatch, styrene-isoprene copolymer and antioxidant, and the mass fraction of isoprene in the styrene-isoprene copolymer is 12%.
[0085] Performance Testing
[0086] The following tests were performed on the tough PE pipes prepared in various embodiments and comparative examples of the present application.
[0087] Pressure test: Refer to GB / T 18476 "Determination of crack growth resistance of polyolefin pipes for fluid transportation. Test method for slow crack growth of notched pipes (notch test)", and measure the hydrostatic failure time of tough PE pipes. The longer the failure time, the better the slow crack growth resistance of the pipe, that is, the better the ability to withstand brittle failure.
[0088] Impact resistance test: Refer to GB / T 18743 "Simply supported beam impact test method for thermoplastic pipes for fluid transportation" to measure the impact strength of tough PE pipes.
[0089] UV aging test: refer to GB / T 16422.3 "Plastics laboratory light source exposure test method Part 3: Fluorescent UV lamp", age 50 times with the exposure cycle conditions of cycle number 1, and then perform impact test, measure the impact strength of the PE pipe after aging, and calculate the impact strength retention rate. The retention rate is calculated as follows: impact strength before aging / impact strength after aging × 100%.
[0090] Hot and cold aging test: The tough PE pipe is placed in a hot and cold water cycle test box and cycled 1000 times. Each cycle includes 15 minutes of cold water and 15 minutes of hot water. The cold water temperature is 4±1℃ and the hot water temperature is 60±1℃. Then an impact test is carried out to measure the impact strength of the tough PE pipe after aging, and the impact strength retention rate is calculated. The retention rate is calculated as follows: impact strength before aging / impact strength after aging × 100%.
[0091] The above test results are shown in Table 1 and Table 2.
[0092] Table 1
[0093] Hydrostatic failure time (h) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 1188 28.1 Example 2 1284 29.2 Example 3 1248 29.6 Example 4 1248 28.9 Example 5 1200 28.2 Example 6 1308 29.3 Example 7 1284 29.0 Example 8 1320 30.3 Example 9 1308 29.9 Comparative Example 1 852 20.5 Comparative Example 2 888 21.8 Comparative Example 3 984 23.6 Comparative Example 4 924 21.3
[0094] Table 2
[0095]
[0096]
[0097] Combining Table 1 and Table 2, it can be seen that the hydrostatic failure time of the tough PE pipes prepared in Examples 1-3 all reached more than 1100 hours, with good brittle failure resistance, high impact strength, good overall mechanical properties, and after ultraviolet aging or hot and cold aging, it can still achieve an impact strength retention rate of more than 91%, and has good durability.
[0098] Combining Example 3 with Comparative Examples 1-2, Comparative Example 1 and Comparative Example 2 lack ethylene-methacrylic acid copolymer and nucleating agent respectively, it is found that the pipe has different degrees of reduction in brittle failure resistance, impact strength and resistance to cold and hot aging, indicating that the addition of ethylene-methacrylic acid copolymer and nucleating agent has a significant effect on the uniformity of carbon black masterbatch and the dispersibility of carbon black in the polyethylene system.
[0099] Combining Example 3 with Comparative Examples 3-4, the difference between Comparative Examples 3 and 4 and Example 3 is that the addition method of styrene-olefin copolymer is different. It can be seen that not only the brittle failure resistance, impact strength and resistance to cold and hot aging of the pipe will be reduced, but also the resistance to ultraviolet aging will be significantly reduced, indicating that styrene-olefin copolymer in carbon black masterbatch or in the outer layer will affect the role of carbon black in resisting light degradation, resulting in insufficient corresponding ultraviolet resistance.
[0100] Combining Examples 5-7 with Example 3, it can be seen that the composite nucleating agent composed of wollastonite modified by a vinyl silane coupling agent and potassium stearate can effectively prolong the hydrostatic failure time, that is, improve the brittle failure resistance.
[0101] Combining Examples 8-9 with Example 3, it can be seen that when the mass fraction of isoprene in the styrene-isoprene copolymer is selected to be 20-27%, the brittle failure resistance of the pipe can be improved, and the UV resistance can also be improved.
[0102] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A tough PE pipe, characterized in that: The invention comprises an inner layer and an outer layer, wherein the inner layer is made of raw materials including LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant, and the outer layer is made of raw materials including HDPE, carbon black masterbatch and antioxidant; the weight ratio of LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant in the inner layer is 100:(5-8):(2-4):(0.5-0.8); the weight ratio of HDPE, carbon black masterbatch and antioxidant in the outer layer is 100:(6-10.5):(0.5-0.8); The carbon black masterbatch is made from the following raw materials in parts by weight: Carbon black 8-16 parts; LDPE 13~22 parts; 0.45-0.8 parts of ethylene-methacrylic acid copolymer; 0.1-0.25 parts of styrene-acrylic acid copolymer; Nucleating agent 0.05~0.1 parts.
2. A tough PE pipe according to claim 1, characterized in that: The mass fraction of methacrylic acid in the ethylene-methacrylic acid copolymer is 9-12%.
3. A tough PE pipe according to claim 1, characterized in that: The styrene-olefin copolymer is selected from one or both of styrene-butadiene copolymer and styrene-isoprene copolymer.
4. The tough PE pipe according to claim 1, characterized in that: The styrene-olefin copolymer is selected from styrene-isoprene copolymer, and the mass fraction of isoprene in the styrene-isoprene copolymer is 20-27%.
5. The tough PE pipe according to claim 1, characterized in that: The nucleating agent is selected from one or more of talc, wollastonite, silicon dioxide, sorbitol nucleating agents and stearate nucleating agents.
6. The tough PE pipe according to claim 1, characterized in that: The nucleating agent is a combination of vinyl silane coupling agent modified wollastonite and potassium stearate in a weight ratio of 1: (3-5).
7. A method for preparing a tough PE pipe according to any one of claims 1 to 6, characterized in that: The following steps are involved: Carbon black, LDPE, ethylene-methacrylic acid copolymer, styrene-acrylic acid copolymer and nucleating agent are put into an extruder for mixing, extruding, cooling and granulating to obtain a carbon black masterbatch; LDPE, carbon black masterbatch, styrene-olefin copolymer and antioxidant are used as inner layer raw materials and put into an extruder for extrusion to obtain an inner layer fluid, HDPE, carbon black masterbatch and antioxidant are used as outer layer raw materials and put into another extruder for extrusion to obtain an outer layer fluid, and then the inner layer fluid and the outer layer fluid are compositely co-extruded through a co-extrusion die head, cooled, and a tough PE pipe is obtained.
8. The method for preparing a tough PE pipe according to claim 7, characterized in that: The nucleating agent is a combination of vinyl silane coupling agent modified wollastonite and potassium stearate in a weight ratio of 1:(3-4). The preparation method of the vinyl silane coupling agent modified wollastonite is as follows: wollastonite is dispersed in a solvent, a vinyl silane coupling agent is added, heated for reaction, and filtered after the reaction is completed to obtain the vinyl silane coupling agent modified wollastonite.
Citation Information
Patent Citations
Double wall corrugated pipe
CN102002179A
Antibacterial double-layer polyethylene tube
CN102848607A